2019
DOI: 10.3390/toxins11100609
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Aflatoxin B1 and Zearalenone by Bacterial and Fungal Laccases in Presence of Structurally Defined Chemicals and Complex Natural Mediators

Abstract: Aflatoxin B1 (AFB1) and zearalenone (ZEN) exert deleterious effects to human and animal health. In this study, the ability of a CotA laccase from Bacillus subtilis (BsCotA) to degrade these two mycotoxins was first investigated. Among the nine structurally defined chemical compounds, methyl syringate was the most efficient mediator assisting BsCotA to degrade AFB1 (98.0%) and ZEN (100.0%). BsCotA could also use plant extracts, including the Epimedium brevicornu, Cucumis sativus L., Lavandula angustifolia, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 55 publications
4
37
0
Order By: Relevance
“…Our study showed similar results that buffers at pH 8.0, 9.0 and 10.0 were responsible for AFB 1 degradation without laccase ( Figure 3 D). The extent of AFB 1 degradation catalyzed by Lac 2 at pH 7.0 would be much greater than that in acidic buffers, which was similar to findings on CotA laccase from B. subtilis [ 20 ], but different from T. versicolor laccase with an optimal pH of 4.5. Furthermore, ABTS was studied as the substrate for the stability of Lac 2.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Our study showed similar results that buffers at pH 8.0, 9.0 and 10.0 were responsible for AFB 1 degradation without laccase ( Figure 3 D). The extent of AFB 1 degradation catalyzed by Lac 2 at pH 7.0 would be much greater than that in acidic buffers, which was similar to findings on CotA laccase from B. subtilis [ 20 ], but different from T. versicolor laccase with an optimal pH of 4.5. Furthermore, ABTS was studied as the substrate for the stability of Lac 2.…”
Section: Discussionsupporting
confidence: 81%
“…The open reading frame (ORF) of lac 2 gene encoded a full-length protein of 512 amino acids with an estimated molecular mass of about 60 kDa, which is in the range of molecular masses of most fungal laccases with regular three domains (50-70 kDa) [25]. Reports on laccases responsible for AFB 1 degradation include the following: BsCotA from B. subtilis (Accession: AID81987.1) [20], laccase from T. versicolor (Accession: CAA77015.1 [21], PDB code: 1KYA [26,27]); Lac 2 from P. pulmonarius (Accession: AAX40733.1) [22]; and Ery4 from P. eryngii (Accession: CAO79915.1) [29]. Researchers have been trying to investigate the mechanism by employing both molecular techniques and direct analysis of degradation products.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations